Penggunaan Media Sosial dalam Meningkatkan Kinsentrasi Belajar Siswa (Studi Kasus Siswa SDN Tegalwaru dan SDN Warung Jeruk 1) - Yun Sri Wahyuni; Neng Evi Nurfaidah; Suharyanto H. Soro; Ida Tejawiani (Civiliza Publishing, Indonesia., 2026)
Social media as an instrument is used in communicating, obtaining information, and accessing entertainment. However, uncontrolled use has the potential to reduce students' concentration in learning during the learning process. This study aims to describe the use of social media in improving students' concentration in learning. Researchers used a case study approach. Data collection methods were carried out through observation, interviews, and documentation with respondents who were principals, teachers, students, and parents of students. The results of the study showed that (1) In general, students use social media every day with varying durations, ranging from 1 to more than 4 hours; (2) The most widely used platforms are TikTok, YouTube, WhatsApp, and Instagram; (3) Increasing the frequency of social media use causes students to be more distracted while studying, have difficulty maintaining focus for a long time, pay less attention to teacher explanations, and experience decreased concentration when doing assignments and participating in class; (4) The habit of accessing social media during study time and before bedtime affects students' readiness to participate in learning activities at school. This study concluded that the use of social media can reduce students' concentration in learning in elementary schools. The higher the intensity of social media use, the greater the potential for disrupting students' concentration in learning.